The Fiscal Multiplier of Public Investment : The Role of Corporate Balance Sheet - Espinoza, Raphael (IMF Working Papers; Working Paper, 2020)
This paper explores whether public investment crowds out or crowds in private investment. To this aim, we build a database of about half a million firms from 49 countries. We find that the effect of public investment on corporate investment depends both on leverage and financial constraints. Public investment boosts private investment for firms with low leverage. However, for firms with high leverage, private investment does not react to an increase in public investment, in line with theory (Myers 1977). We also find that the effect of public investment on corporate investment is much weaker for firms that are financially constrained.